Effect of sulphur on growth and yield of sunflower (Helianthus annuus L.) and blackgram (Phaseolus mungo L.) in intercropping system - Kumar, Promod; Thenua, O.V.S. (Annals of Agricultural Research, 2014)
Two year field experiments were conducted during kharif 2006 and 2007 at the research farm of A.S. Post Graduate College, Lakhaoti to find out suitable planting pattern for sunflower and blackgram under intercropping for increased productivity and land use efficiency. The experiment was laid out in split plot design with 3 replications. Quadratic response function was fitted to define the relationship between the seed yield and sulphur application and total productivity (sunflowerequivalent) and sulphur application. The optimum economic dose of sulphur computed for sunflower and blackgram intercropping was 56.0 kg/ha.